Pengaruh Latihan Senam Kegel Terhadap Frekuensi Berkemih Pada Lansia - Wahyudi, Agus Setyo; , Sulastri, S.Kp.,M.Kes; , Arif Wahyudi Jadmiko S.Kep., Ns., M.Kes (2017)
One of the problems of elderly is urine incontinence. Urine frequency by elderly more than 8 time a day. Data pre study in in nursing home Darma Bakti Pajang of Surakarta known 31 elderly had experienced urine incontinence. One effort to overcome. the objectives was to know influence of kegel exercise to urine frequency of elderly. Design research use quasi experiment design with pretestposttest one group design. The sample was 44 elderly who living in nursing home Darma Bakti Pajang of Surakarta. Taking sample used simple random sampling. Data then tested with wilcoxon test. The results of the study that pre test 32 respondents with urine frequency in normal category, 12 respondents abnormal. There were 41 respondents with urine frequency in of normal category in post test, while 3 elderly included in abnormal. The results of the analysis test Wilcoxon with value p = 0,001, it means there was an influence of exercise kegel to urine frequency of elderly in nursing home Darma Bakti Pajang of Surakarta.